2001
DOI: 10.1007/bf02255973
|View full text |Cite
|
Sign up to set email alerts
|

Mammalian alcohol dehydrogenase — Functional and structural implications

Abstract: Mammalian alcohol dehydrogenase (ADH) constitutes a complex system with different forms and extensive multiplicity (ADH1-ADH6) that catalyze the oxidation and reduction of a wide variety of alcohols and aldehydes. The ADH1 enzymes, the classical liver forms, are involved in several metabolic pathways beside the oxidation of ethanol, e.g. norepinephrine, dopamine, serotonin and bile acid metabolism. This class is also able to further oxidize aldehydes into the corresponding carboxylic acids, i.e. dismutation. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
43
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(44 citation statements)
references
References 17 publications
1
43
0
Order By: Relevance
“…The second split was between ADH1A and ADH1B. These results agree with our preliminary analyses using the neighbour joining (NJ) tree (Saitou and Nei, 1987) including all ADH classes based on cDNA and amino acid sequences from human, baboon, horse, mouse, rat, fish, amphioxus, and E. coli plasmid (tree not shown) derived from databases, and also with previously reported trees (Yokoyama and Yokoyama, 1987;Höög et al, 2001).…”
Section: Phylogenetic Topology and Rootingsupporting
confidence: 92%
See 1 more Smart Citation
“…The second split was between ADH1A and ADH1B. These results agree with our preliminary analyses using the neighbour joining (NJ) tree (Saitou and Nei, 1987) including all ADH classes based on cDNA and amino acid sequences from human, baboon, horse, mouse, rat, fish, amphioxus, and E. coli plasmid (tree not shown) derived from databases, and also with previously reported trees (Yokoyama and Yokoyama, 1987;Höög et al, 2001).…”
Section: Phylogenetic Topology and Rootingsupporting
confidence: 92%
“…All ADH classes form dimers and catalyze oxidization of various kinds and concentrations of alcohols using NAD + /NADH as coenzyme (Eklund et al, 1976a,b;Höög et al, 2001). The ADH family is classified into five classes (I-V) based on biochemical properties, and nucleotide/amino acid sequence similarity.…”
Section: Introductionmentioning
confidence: 99%
“…Alcohol dehydrogenase 3 (ADH3), the ancestral form within the mammalian alcohol dehydrogenase system, is also known as glutathione-dependent formaldehyde dehydrogenase and S-nitrosoglutathione (GSNO) reductase [1][2][3][4]. The latter reflects the dual function of the enzyme [5].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the enzyme shows a universal presence and structural conservation that imply that ADH3 performs essential functions in many living organisms [6]. Functions attributed to ADH3 include first-pass ethanol metabolism, detoxification of endogenous and exogenous formaldehyde, nitric oxide (NO) homeostasis, contribution to retinoic acid formation, and oxidation of x-hydroxy fatty acids [1,5,[7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Höög et al [14] reported the functions of ADH1-ADH4 and cautioned that rodents are poor model systems for human ethanol metabolism since the rodent ADH2 enzymes almost lack ethanol-oxidizing capacity in contrast to the human form. The authors further proposed that, in contrast to the cytochrome P450 system, the function of the entire ADH system could be seen as a general detoxifying system for alcohols and aldehydes without generating toxic radicals.…”
Section: Structure and Function Of Alcohol Dehydrogenasesmentioning
confidence: 99%